If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -2) + 2(x + -1) = 0 Reorder the terms: (-2 + 5x) + 2(x + -1) = 0 Remove parenthesis around (-2 + 5x) -2 + 5x + 2(x + -1) = 0 Reorder the terms: -2 + 5x + 2(-1 + x) = 0 -2 + 5x + (-1 * 2 + x * 2) = 0 -2 + 5x + (-2 + 2x) = 0 Reorder the terms: -2 + -2 + 5x + 2x = 0 Combine like terms: -2 + -2 = -4 -4 + 5x + 2x = 0 Combine like terms: 5x + 2x = 7x -4 + 7x = 0 Solving -4 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 7x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 7x = 0 + 4 7x = 0 + 4 Combine like terms: 0 + 4 = 4 7x = 4 Divide each side by '7'. x = 0.5714285714 Simplifying x = 0.5714285714
| 57=w/3 | | 4(w-2)-w=46 | | sqrtx^4+18x^3+6=3 | | 4x/4=-13/4 | | -(2x-4)-4(x+5)= | | 7x-4=4(x-3) | | 0x=-13 | | 4y+xy+6x+(x*x)+8=z | | 28x+9=9x+41 | | -2(5x+4)-5(4x-3)= | | 10+10k=4k-10-10 | | 100/365 | | -5(2x+3)-(2x+1)= | | (10s^5)(7st^4)= | | 7-(3+5)= | | -1+7u=-10+10u | | -2(4x-3)+5(2x-1)= | | y/-8=10 | | 7(x+8)-32= | | -4v+8=5v-10 | | 128-3z/5 | | 4(5x-1)-5(5x-3)= | | 3x-6+6x+12=12x-24 | | 16/72=x/1416 | | -3+6=39 | | 4.9t^2-26t-10=0 | | 6f+2=20 | | -6(3x-5)=19(7-x) | | -6m+3=10-5m | | -2(3x+5)+4(2x+2)= | | 2x^3-10x^2-100x=72 | | 4y-4+y+24=6y-20-4y |